Correction: A new family of fullerene derivatives: fullerene–curcumin conjugates for biological and photovoltaic applications. Issue 5 (18th January 2019) - Castro, Edison; Cerón, Maira R.; Garcia, Andrea Hernandez; Kim, Quentin; Etcheverry-Berríos, Alvaro; Morel, Mauricio J.; Díaz-Torres, Raúl; Qian, Wenjie; Martinez, Zachary; Mendez, Lois; Perez, Frank; Santoyo, Christy A.; et al.
Abstract : Correction for 'A new family of fullerene derivatives: fullerene–curcumin conjugates for biological and photovoltaic applications' by Edison Castro et al., RSC Adv., 2018, 8, 41692–41698.